A variant of Jensen-type inequality and related results for harmonic convex functions - Abbas Baloch, Imran; Ahmad Mughal, Aqeel; Chu, Yu-Ming; Ul Haq, Absar; De La Sen, Manuel (AIMS mathematics, 2020)
In this article, we present a variant of discrete Jensen-type inequality for harmonic convex functions and establish a Jensen-type inequality for harmonic h-convex functions. Furthermore, we found a variant of Jensen-type inequality for harmonic h-convex functions.